Effects of Adaptive, Organizational Learning and Absorbability and Their Impact on Marketing Capabilities and Business Performance: Unlocking the Potential of Indonesian Non-high-tech SMEs - Kholid Mawardi, Mukhammad; supriono, supriono (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This study aims to exploit the factors that influence business performance in the context of non-high-tech SMEs. This study investigates the mechanism by which the capabilities of SMEs are applied to improve business performance. The study focuses on the mediating role of marketing ability in the relationship between adaptive capability, organizational learning capability, and absorptive capacity in marketing and business performance. Research models were developed to link key constructs of business capabilities with business performance. Structural equation modelling was applied to test the model using data collected from 160 respondents in Malang City, Indonesia. The results show that organizational learning capability can affect marketing capability and that marketing capabilities affect the business performance of non-high-tech SMEs. Marketing capability can mediate the relationship between organizational learning capability and business performance. The study limits the possibility of generalizing the findings, focusing on Malang City and non-high-tech SMEs. Therefore, the scope of research needs to be increased by expanding the research context and adding high-tech SMEs as an additional variety of research discussions. This study makes an important contribution to the SME literature body by identifying the mediating effect of marketing capabilities on the relationship between business capabilities and business performance.